2022
DOI: 10.3389/fcvm.2022.869505
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evaluation of Embedded Modular Single-Branched Stent Graft: Application to Type B Aortic Dissection With Aberrant Right Subclavian Artery

Abstract: BackgroundEndovascular repair of type B aortic dissection (TBAD) with aberrant right subclavian artery (ARSA) is challenging due to anatomical complexity. The embedded modular single-branched stent graft (EMSBSG) could solve this problem. However, the hemodynamic efficacy of this innovative technique has not been fully assessed. This study aimed to propose morphometric and functional indicators to quantify the outcomes of EMSBSG in treating TBAD with ARSA.Material and MethodsA patient who had TBAD with ARSA un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Single-branched stents can be used for ARSA reconstruction as well. Zhang et al (21) reported the application of an embedded modular single- branched stent for endovascular repair of TBAD with ARSA; however, this device has not seen widespread adoption. In recent years, a single-branched stent graft named "Castor", specifically designed for TBAD involving LSA, has been widely used and has achieved satisfactory results (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Single-branched stents can be used for ARSA reconstruction as well. Zhang et al (21) reported the application of an embedded modular single- branched stent for endovascular repair of TBAD with ARSA; however, this device has not seen widespread adoption. In recent years, a single-branched stent graft named "Castor", specifically designed for TBAD involving LSA, has been widely used and has achieved satisfactory results (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…These factors collectively increase the propensity for thrombus. Consequently, these parameters can be employed as valuable tools to assess the long-term risks associated with arterial diseases [ 22 , 23 ]. By understanding the short-term and long-term risks of RAS, clinicians can better evaluate the necessity of interventional treatments for moderate RAS.…”
Section: Introductionmentioning
confidence: 99%